New thinking for the next generation of antimalarials - Hannah Asiki; Jason Hlozek; Kathryn J Wicht; John G Woodland; Kelly Chibale (EMBO Molecular Medicine, 2026)
Abstract Despite decades of intensive research and substantial clinical gains, malaria remains a major global health challenge exacerbated by the continued emergence of drug-resistant strains of the causative agent, Plasmodium parasites. Encouragingly, recent advances in functional genomics, chemical biology and computational science are reshaping antimalarial drug discovery. In this review, we examine the discovery and development of next-generation antimalarials, including advances in phenotypic and target-based screening, omics-enabled target discovery and emerging therapeutic modalities such as long-acting agents, targeted covalent inhibitors and host-directed therapies. We further evaluate the opportunities and limitations of drug repurposing and discuss how artificial intelligence and data-driven approaches are reshaping target identification, compound optimisation and clinical development. Finally, we argue that future success will depend not only on scientific innovation but also on interdisciplinary collaboration, equitable partnerships, open science and the development of accessible therapies tailored to malaria-endemic populations.